Toujours est-il que (p) ou le retour à un topique antérieur - Véronique Lenepveu (Discours)
In this paper, we propose a semantic and pragmatic analysis of the French lexicalized expression toujours est-il que which marks a return to the main discourse topic (Van Dijk, 1976; Charolles, 2003). At first, through the analysis of real examples and of their typical context, it is shown that this lexicalized expression expresses a de dicto aspectual value (Martin, 1987). Then, we show it is necessary to take into account the de dicto value of this locution in order to study the information structure of discursive patterns in which it is employed. In this locution, the aspectual adverb toujours does not concern the content anymore, but the speaker’s commitment. It indicates that the initial point of view (Nølke, 1994) is still valid (persistence value), in spite of what has been said meanwhile.